Bioactivity of Endophytic Fungi Fusarium brachygibbosum Isolated from the Stem of Avicennia marina as a Candidate for New Drug Source - Oktiansyah, Rian; Noviyanto, Noviyanto; Iskandar, Damayanti; Nasution, Sakinah Salman Ahmad; Laksono, Pandu Jati; Kurniawati, Alfia Rahma; Pancasari, Adelia Rizki; Aputri, Farah Nuriessa; Yogyaswari, Sekar Ayoe (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
Indonesia's biodiversity holds significant potential as a source of medicinal compounds, one of which is Avicennia marina, known for its antioxidant and antibacterial properties. However, due to its protected conservation status, its utilization is limited. An alternative approach to harness its benefits is through symbiotic microorganisms such as endophytic fungi. This study aimed to isolate and evaluate the bioactivity of the endophytic fungus Fusarium brachygibbosum isolated from the stem of A. marina as a potential source of novel therapeutic agents. The methodology involved fungal isolation, morphological identification, and evaluation of antibacterial activity using the disc diffusion method and antioxidant activity using the DPPH assay. The results demonstrated that the obtained isolate (coded ADM2) exhibited strong antibacterial activity against Escherichia coli, Staphylococcus aureus, Salmonella typhi, and Bacillus subtilis. Moreover, the antioxidant assay of the ADM2 isolate revealed a very strong potential (IC50 < 20 µg/mL), indicating its potent ability to scavenge free radicals. Based on these findings and the literature on F. brachygibbosum, this species shows great potential as a source of bioactive compounds with medical applications, particularly in treating infections and preventing degenerative diseases. Further in vivo studies are necessary to confirm the therapeutic potential of this fungus as a safe and effective drug candidate.